The Effect of Foot Massage on Quality of Sleep in Elderly - Wahyu, Afrianti; Kurniawati, Dwi (Poltekkes Kemenkes Surakarta, 2025)
Background: Sleep disruptions and pattern alterations are more common in the elderly. The physical well-being, mental clarity, and overall quality of life of the elderly can all be greatly impacted by these changes. The following are some of the main problems with the elderly's sleep quality. The objective of this research is to determine the effect of foot massage on quality sleep in the elderly. Methods: Quasi-experimental research with pretest and posttest control group design approach. Participants were selected using a non-probability purposive sampling technique based on inclusion criteria related to age and sleep disturbances, with a total of 25 elderly individuals. Subjects were randomly divided into 2 groups. Group I receives the foot massage treatment and group II is the control group. This study measured the quality of sleep in the elderly. The research instrument used the Pittsburgh Sleep Quality Index (PSQI). Results: The analysis includes 25 participants, divided into two groups. In Group 1, all 14 participants showed a decrease in sleep quality scores, which is statistically significant (p<0.001). In group II, the change is not statistically significant (p=0.724), indicating that most participants did not experience substantial changes in sleep quality. Conclusion: Foot massage is a non-pharmacological intervention demonstrated to enhance sleep quality among elderly individuals. The analysis indicates that foot massage significantly enhances blood circulation and muscle relaxation, contributing to improved sleep quality. This intervention shows potential as a practical and non-pharmacological method for managing sleep disturbances in the elderly.